ARGUMENTATIVE DIMENSIONS OF EPISTEMOLOGICAL RELATIVISM: BETWEEN THE PROGRAM AND SCEPTICAL DOUBT (Andamios, Revista de Investigación Social, 2009)
The aim of this paper is to open the debate on the implications that epistemic relativism has as a form to understand the scientific activity. One looks for to analyze the strategies to argue which this one faces the universalist and rationalist positions in epistemology; and to see how from these it bases a program or agenda of work for which they try to give account of how science is constructed. In this essay we argue that a characteristic of the relativists arguments has made difficult to its critic or the attempts to avoid it, is that it leaves from a set of skeptical arguments with which fights the universalist and rationalist pretensions of other traditions in the philosophy of science.
Keywords: Relativism; pluralism; scepticism; rationalism; universalism